1970
DOI: 10.1111/j.1365-2621.1970.tb01990.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Carbonyl and Sulfur Compounds From Nonenzymatic Browning Reactions of Glucose and Sulfur‐containing Amino Acids

Abstract: SUMMARY– Odor evaluations, chemical analyses and the effect of pH on the nonenzymatic browning reaction products between equimolar concentrations of glucose and each of the sulfurcontaining amino acids, methionine, cysteine and cystine, were conducted. None of the 3 mixtures emitted an odor associated with meat. The cystine‐glucose mixture produced no significant aroma, the cysteine‐glucose mixture an odor resembling over‐boiled egg and the methionine‐glucose mixture an objectionable odor associated with boile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The lysine and tryptophan systems alone and in combination showed less than a 0.1 pH decrease or rise at both temperatures over this time. The decrease in the cysteine system could be due to the production of mercaptans (Song and Chichester 1967;Arroyo and Lillard 1970). It has been found that the browning rate for amino acids in solution is at a minimum in the pH 3.5 to 4.0 range (Labuza and Schmidl, 1986) and thus the decrease in browning rate could be due to this pH decrease.…”
Section: Results and Discussion Brown Pigment Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The lysine and tryptophan systems alone and in combination showed less than a 0.1 pH decrease or rise at both temperatures over this time. The decrease in the cysteine system could be due to the production of mercaptans (Song and Chichester 1967;Arroyo and Lillard 1970). It has been found that the browning rate for amino acids in solution is at a minimum in the pH 3.5 to 4.0 range (Labuza and Schmidl, 1986) and thus the decrease in browning rate could be due to this pH decrease.…”
Section: Results and Discussion Brown Pigment Formationmentioning
confidence: 99%
“…In previous studies on NEB in TPN solutions held at room temperature for 3 to 6 weeks, tryptophan has been reported to have the greatest decrease in concentration with time, although it has only one available amine group (Jurgens et al, 1981;Fry and Stegink, 1982). Studies have shown that cysteine inhibits NEB (Montgomery, 1983;Arroyo and Lillard, 1970;Song and Chichester, 1967), but the role of cysteine as an inhibitor of NEB in TPN solutions has not been documented. The purpose of this study was to determine the effects of interactions between three key amino acids, lysine, cysteine and tryptophan as a function of storage temperature and the presence of electrolytes on the rate of NEB in model TPN systems.…”
Section: Introductionmentioning
confidence: 99%
“…A bitter off-flavor of hard-cooked eggs develops with the increase of the Maillard reaction (Baker and Darfler, 1969). Arroyo and Lillard (1970) screened several sulfur-containing amino acids in reaction with glucose.…”
Section: Peel Ability Of Hard-cooked Eggsmentioning
confidence: 99%
“…Binding an amino acid to a monosaccharide forms S-, O-or Nglycosides [15]. Sulfur-containing volatile compounds, thermally generated from cysteine in the presence of glucose, have been reported [16,17]. On the other hand, water, alcohols, thiols and amines additives to the carbonyl group have been rather extensively studied [18,19].…”
Section: Introductionmentioning
confidence: 99%